Changes in social work students' attitudes and knowledge following opioid overdose prevention training. Issue 1 (1st December 2022) - Halmo, Rebekah S.; Sellers, Christina M.; Collin, Cali-Ryan R.; Chinamasa, Gordon; Putney, Jennifer M.
Abstract: Background: Opioid use disorders are widespread, commonly occurring, and have serious impacts on individuals, families, and communities. When adequately trained, social workers play a pivotal role in treating populations impacted by opioid use through the provision of high-quality services and the shifting of negative attitudes related to opioid use. However, workforce projections indicate a growing shortage of behavioral health professionals qualified to work with such populations and, presently, social work programs are not equipped to meet these workforce needs. Emerging evidence suggests opioid overdose education is associated with improved attitudes and knowledge among health professions; however, less information exists on the outcomes of such training among social work students. Schools of social work must develop and evaluate curricular components related to opioid use prevention and management to adequately prepare students for clinical work as social work practitioners. Methods: Thirty-three advanced-year MSW students received opioid overdose training as part of a day-long seminar on substance use. Content included acute effects of opioids, withdrawal symptoms, risk factors, signs of overdose, naloxone training, and harm reduction principles. Using a single-group pretest-posttest design, students completed the Opioid Overdose Attitudes Scale (OOAS) and the Opioid Overdose Knowledge Scale (OOKS). To evaluate students' attitudes and knowledge, investigators compared overall and subscale means before and after the training via paired samples t -tests. Results: Findings indicated statistically significant improvements in the "concerns" and "competence" domains of the OOAS. Likewise, findings indicated statistically significant improvements in the "risk, " "signs, " "action, " and "naloxone use" domains of the OOKS. Conclusion: Students reported improved opioid overdose-related knowledge and attitudes when assessed after the training as compared to before the training. Due to the nature of the study design, causality cannot be inferred from the training outcomes. Findings may help other social work programs develop curricular components related to opioid use.